Structural and chemical heterogeneity of colloform cassiterite and In, Pb, As minerals at the tin ores for the Verkhnee deposit (Primorye, Russia) - N. V. Gorelikova; V. I. Taskaev; V. A. Rassulov (Известия высших учебных заведений: Геология и разведка, 2019)
The colloform tin ores from the deposit Verkhnee at the Primorye have been studied with the aid of X- ray spectroscopic microanalysis and the scanning electron microscopy with the energy dispersive analyzer LINK-ISIS that allowed revealing the primary and the secondary zoning of a colloform cassiterite and to determine the phase composition of these formations. The primary zoning of the mineral forms at the early stage of the deposition of stannates from colloidal solutions and is characterized by the alternation of hydrostannates of various composition. The secondary zoning is superimposed zonality, and it forms at the process of the stannate crystallization. The metacolloidal varieties of concentric-zonal aggregates are produced by hydrostannates of Ca, Fe, Cu, In, of variable compositions, soluble in acids, in which the admixtures of As, Al, Si, Cd, Co, Sb, Zn, Ag are marked. Sn content according to the energy dispersive analysis is 42—54%. Infrared adsorption spectroscopy allowed finding out in hydrostannates the presence of the hydroxyl water at the area of the valence vibrations Sn-OH. In the colloform cassiterite a new phase Pb5 As2 O8 with various correlation of Pb and As in size 30—50 mk has been found.